(untitled) (Philology, 2022)
This article is an attempt to shed light on the causes of the widespread spread of English around the world by turning it into a global language and Global English. The criteria according to which a language can be considered a global language are set out. Its status inevitably has an impact on both the population of English-speaking countries and those who study it as a foreign language.